Theta Cone Metric Spaces and Some Fixed Point Theorems - Sahar Mohamed Ali Abou Bakr (Journal of Mathematics)
This paper introduces the concept of the theta cone metric, studies its various topological properties, and gives some examples of it. Furthermore, it proves some lemmas and then uses them to give further generalizations of some well-known fixed point theorems. Specifically, Theorem 2 of the paper is a generalization of Reich’s fixed point theorem.